Pro: Can neuropathology really confirm the exact diagnosis? - Esiri, M (2010)
Recent advances in the clinical diagnostic instruments for diagnosing Alzheimer's disease (AD) and in neuroimaging may cast doubt in the minds of some practitioners about the continued need for neuropathology to provide the ultimate diagnosis. Certainly the majority of cases of AD can be clinically correctly diagnosed by experienced clinicians but many cases are given this label by less experienced practitioners. Even after the most thorough work-up, a few cases of confidently diagnosed AD turn out to be something else when microscopy of the brain is undertaken. Even for neuropathologists, however, it can be difficult to correctly assign cognitive decline to the various pathological processes that can be found together in an older brain. We need further clinicopathogical study to enlighten us about, for example, the contribution of commonly found cerebrovascular disease to dementia. Human studies are also needed to explore the changes in pathology that new treatments for AD may produce.